Counterfeiting: conceptual issues and implications for branding. Issue 6 (16th September 2019) - Evans, Bradley P.; Starr, Richard G.; Brodie, Roderick J.
Abstract : Purpose: This paper aims to apply a broader perspective of branding to foster new insights and develop strategies to address product counterfeiting. Design/methodology/approach: A review of the counterfeiting and branding literature leads to the development of a new conceptual framework that incorporates proactive, collaborative processes, in addition to the traditional product branding approach. Findings: The integrative framework provides a basis to develop innovative, proactive strategies that complement traditional branding approaches to address product counterfeiting. The complexity of an integrative framework (or network) offers more opportunities for the firm to co-create robust meaning with multiple stakeholders. Identity elements are readily copied, whereas meanings are not. These strategies help to control counterfeiting by developing deep and inimitable relationships between managers and other stakeholders in a marketing network. Research limitations/implications: A research agenda is proposed to structure future studies on counterfeiting. Practical implications: The framework outlines how to leverage collaboration between managers and brand stakeholders to complement conventional approaches to control counterfeiting based on traditional product branding. Originality/value: This paper contributes to the growing body of counterfeiting and brand protection literature by adapting and applying contemporary integrative branding concepts, leading to novel strategies to address the issue.